ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI SIKAP KONSUMEN PADA IKLAN DIGITAL DI INDONESIA - Wandoko, Wanda; Panggati, Ignatius Enda (Infotech: Journal of Technology Information, 2019)
Marketing has now evolved from marketing that focuses on the concept of exchange to the concept of integrated marketing communication (IMC) or marketing communication that is integrated and focuses on relationships with consumers. The development of information technology and the internet plays a major role in the world of IMC, especially in the part of the advertising world, where technology information and the internet developed advertisements into digital advertisements. This study aims to create a research model as a solution to the problem of how to make consumer attitudes towards digital advertising in Indonesia more positive. This study raises consumer attitudes on digital advertising in Indonesia as variables that provide solutions, namely the entertainment (informational) variable, informativenes (informativeness), and credibility as the antecedent variable of consumer attitudes towards digital advertising (ATDID), and the purchase intention variable as an impact of consumer attitudes towards digital advertising. The results of this study are the research model framework, and the operationalization of variables that can be used to conduct quantitative research, with the aim of finding relationships between these variables, which can later be made as a reference in improving consumer attitudes towards digital advertising that are expected to increase buying intentions.